Bake hardening type electrodeposition liquid for three dimensional printer metal shaped article having magnetic function
By using a dry plating solution containing specific copolymers, curing agents, solvents and magnetic powders, the problems of uniformity, adhesion and magnetic functions of electroplating coatings on complex shapes 3D printed metal objects are solved, and high-quality electroplating coating formation is achieved.
Patent Information
- Application Number
- JP2023156619
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-03
AI Technical Summary
The prior art is difficult to form a uniform, strong adhesion and magnetically plating coating on 3D printed metal objects of complex shapes, especially in narrow grooves.
A dry electroplating solution containing a specific copolymer (A), a curing agent (B), a solvent (C) and a magnetic powder (D) is used, which has a hydroxyl group, a carboxyl group or a methylimine group, a water-soluble or water-dispersible, and consists of a specific copolymer, a curing agent and a solvent in a certain proportion.
An electroplating coating with magnetic functions is achieved on 3D printed metal objects of complex shapes, and the coating has good uniformity, adhesion, corrosion resistance and magnetization adsorption.
Smart Images

Figure 2025047865000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a bake-hardenable electrodeposition liquid used for surface coating of complex-shaped metal objects produced by a three-dimensional printer (3D printer) (e.g., metal machines, general metal tools, metal decorations, etc.) having one or more structural parts selected from the group consisting of groove-shaped recesses, cylindrical recesses, polygonal tubular recesses, and lattice structures. [Background technology]
[0002] When excellent adhesion to structures is required, anionic electrodeposition is often used for anodizing, while cationic electrodeposition is often used for automobiles. However, as the shapes of the objects to be painted become more complex, it is becoming increasingly difficult to form a uniform coating with sufficient adhesion even on the walls of narrow recesses. In particular, since many objects created using 3D printers have complex shapes and narrow recesses, there is a demand for the development of electrocoating paints with significantly improved adhesion and uniform coating formation. In particular, electrocoating paints with magnetic properties are desirable for application to actuator parts for industrial robots and other devices that utilize 3D shaping. An anionic electrodeposition coating composition that contains a specific water-soluble or water-dispersible vinyl copolymer, an amino resin, and an alkoxyamine and has excellent coating stability, gloss stability, appearance, and weather resistance has been investigated (Patent Document 1), and a negative cationic electrodeposition photoresist resin composition for electrodeposition coating that contains a specific water-soluble or water-dispersible vinyl copolymer, a copolymerizable vinyl monomer having a specific amino group, a copolymerizable vinyl monomer other than the above, a polyfunctional acrylate having three or more vinyl groups in one molecule, a polyfunctional thiol, and a photopolymerization initiator and has excellent coating stability and sensitivity has been investigated (Patent Document 2), but a satisfactory composition has yet to be obtained. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2006-111687 [Patent Document 2] Patent Publication No. 2016-126174 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has an objective of solving the problems associated with the prior art as described above, and of providing a bake-hardenable electrodeposition liquid that has good viscosity and stability and is capable of forming an electrodeposition coating that has magnetic function and an excellent balance of uniformity, adhesion, corrosion resistance, throwing power, and magnetization adhesion force due to magnetic force on 3D printed metal objects having complex structures, such as those having one or more structural parts selected from the group consisting of groove-shaped recesses, cylindrical recesses, polygonal tubular recesses, and lattice structures (e.g., metal machines, general metal tools, metal ornaments, etc.); a 3D printed metal object with a bake-hardenable electrodeposition coating that uses the bake-hardenable electrodeposition liquid; and a method for forming an electrodeposition coating. [Means for solving the problem]
[0005] As a result of extensive research, the inventors have discovered that a bake-curable electrodeposition liquid for 3D printer metal objects, which contains a specific copolymer (A), a specific curing agent (B), a specific solvent (C), and a magnetic powder (D) in a specific mass ratio, can overcome the above-mentioned problems, and have arrived at the present invention. The present invention is characterized in the following points. 1. A bake-hardening type electrodeposition liquid for 3D printer metal objects, the three-dimensionally printed metal object has one or more structural parts selected from the group consisting of a groove-shaped recess, a cylindrical recess, a polygonal tubular recess, and a lattice structure, The bake-hardening type electrodeposition liquid contains a copolymer (A), a hardener (B), a solvent (C), and a magnetic powder (D), The copolymer (A) is It has a hydroxyl group and a carboxyl group or a tertiary amino group, Water-soluble or water-dispersible, A copolymer of monomer (a), monomer (b), and monomer (c), the mass fraction of the structural portion derived from the monomer (a) in the copolymer (A) is 2 to 15 mass%; the mass fraction of the structural portion derived from the monomer (b) in the copolymer (A) is 2 to 15 mass%; The monomer (a) has a polymerizable carbon-carbon unsaturated bond group and a carboxyl group or a tertiary amino group, The monomer (b) has a polymerizable carbon-carbon unsaturated bond group and a hydroxyl group, the monomer (c) has a polymerizable carbon-carbon unsaturated bond group and is a monomer other than the monomer (a) and the monomer (b); The solvent (C) is an aqueous solvent containing an aqueous organic solvent and water, The bake-hardening type electrodeposition liquid. 2. The mass ratio of the copolymer (A) to the curing agent (B) is 60 / 40 or more and 95 / 5 or less; the total content of the copolymer (A) and the curing agent (B) in the bake-curable electrodeposition solution is 8% by mass or more and 12% by mass or less; The content of the aqueous organic solvent in the bake-hardenable electrodeposition solution is 0.1% by mass or more and 5% by mass or less, the viscosity of the bake-hardenable electrodeposition liquid, measured at 100 rpm using a B-type viscometer equipped with an L-type rotor and a low-viscosity adapter, is 1.50 mPa s or more and 2.70 mPa s or less; 2. The bake-hardenable electrodeposition solution according to 1 above. 3. The copolymer (A) is The glass transition temperature (Tg) is 20 to 40°C. Solubility parameter (SP) value is 10.5 to 11.5 (cal / cm 3 ) 0.5 That is, 3. The bake-hardenable electrodeposition liquid according to 1 or 2 above. 4. The bake hardenable electrodeposition liquid according to any one of 1 to 3 above, wherein the content of the magnetic powder (D) in the bake hardenable electrodeposition liquid is 40 to 170 phr. 5. The monomer (a) has a polymerizable carbon-carbon unsaturated bond group and a carboxyl group, The copolymer (A) has a carboxyl group, The bake-hardening electrodeposition liquid is anionically electrodeposited onto the three-dimensional printer metal object. 5. The bake-hardenable electrodeposition liquid according to any one of 1 to 4 above. 6. The monomer (a) has a polymerizable carbon-carbon unsaturated bond group and a tertiary amino group, The copolymer (A) has a tertiary amino group, The bake-hardening electrodeposition liquid is cationic electrodeposited onto the three-dimensional printer metal object. 6. The bake-hardenable electrodeposition liquid according to any one of 1 to 5 above. 7. A three-dimensional printer metal object having a bake-curable electrodeposition coating film, produced using the bake-curable electrodeposition liquid according to any one of 1 to 6 above. 8. A method for forming an electrodeposition coating film, comprising forming an electrodeposition coating film on a surface of a three-dimensional printed metal object using the bake-hardening electrodeposition liquid according to any one of 1 to 6 above, the three-dimensionally printed metal object has one or more structural parts selected from the group consisting of a groove-shaped recess, a cylindrical recess, a polygonal tubular recess, and a lattice structure, The method includes the following steps (1) to (7) in this order: (1) a process for degreasing the surface of the 3D printer metal object; (2) A process for washing the surface of the 3D printer metal object with water; (3) immersing the 3D printed metal object in the bake-hardenable electrodeposition liquid; (4) removing air bubbles from the surface of the 3D printed metal object; (5) forming an electrodeposition coating film on the surface of the 3D printer metal object; (6) A process of rinsing and draining the electrocoating film; (7) a step of baking and hardening the electrodeposition coating film; Where: Step (3) includes a step of immersing the three-dimensional printer-produced metal object in the bake-hardenable electrodeposition liquid while the surface of the object is wet with water; Step (4) includes a step of stirring the bake-hardenable electrodeposition liquid and moving the three-dimensional printed metal model up and down; Step (5) includes a step of applying the heating agent while stirring the bake-hardenable electrodeposition liquid and while moving the metal object up and down by the three-dimensional printer, The method for forming the electrodeposition coating film. Effect of the Invention
[0006] According to the present invention, there is provided a bake-curable electrodeposition liquid that has good viscosity and stability and is capable of forming an electrodeposition coating film that has magnetic function and an excellent balance of uniformity, adhesion, corrosion resistance, throwing power, and magnetization adhesion force due to magnetic force on a 3D printer metal object (e.g., metal machines, general metal tools, metal ornaments, etc.) having a complex structure, such as one or more structural parts selected from the group consisting of groove-shaped recesses, cylindrical recesses, polygonal tubular recesses, and lattice structures; a 3D printer metal object with a bake-curable electrodeposition coating film using the bake-curable electrodeposition liquid; and a method for forming an electrodeposition coating. [Brief description of the drawings]
[0007] [Figure 1] 1 is an example of a 3D printer metal object having groove-like recesses electrodeposited using the bake-hardening electrodeposition liquid of the present invention. [Diagram 2] 1 is an example of a 3D printer metal object having polygonal recesses, electrodeposited using the bake-hardenable electrodeposition liquid of the present invention. [Diagram 3] 1 is an example of a 3D printer metal object having a lattice structure, electrodeposited using the bake-hardenable electrodeposition liquid of the present invention.
[0008] In each drawing, the size and ratio of the components may be changed or exaggerated for ease of understanding. Also, for ease of understanding, parts that are not necessary for the explanation or repeated reference numerals may be omitted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will now be described in more detail. <Bake-hardening type electrodeposition solution> The bake-hardenable electrodeposition liquid of the present invention has magnetic properties and excellent throwing power, and can be used to uniformly perform electrodeposition coating on 3D printer metal objects (e.g., metal machines, general metal tools, metal decorations, etc.) having complex structures, such as those having one or more types of structures selected from the group consisting of groove-shaped recesses, cylindrical recesses, polygonal recesses, and lattice structures. In addition, electrodeposition coating using the bake-hardening electrodeposition liquid of the present invention can achieve coating that reaches every corner more thoroughly than air spray coating, and is less prone to paint dripping than simple dipping coating.
[0010] The bake-curable electrodeposition liquid of the present invention contains a copolymer (A), a curing agent (B), a solvent (C) and a magnetic powder (D). The bake-curable electrodeposition liquid of the present invention may be a homogeneous solution or an emulsion. The bake-curable electrodeposition liquid of the present invention may further contain a pigment (E). The bake-curable electrodeposition solution of the present invention may further contain, if necessary, a neutralizing agent (F) for ionizing the copolymer (A) to enhance water solubility or water dispersibility. Furthermore, if necessary, the coating composition may contain various types of curing accelerators, or may further contain dyes, fillers, etc. to make the coating film more aesthetically pleasing. In order to improve workability during coating film formation or to impart various functions to the coating film, the coating composition may further contain various additives such as light stabilizers, antioxidants, wetting agents, leveling agents, and defoamers, as well as other resins such as urethane resins and epoxy resins.
[0011] In the bake-curing type electrodeposition solution, the mass ratio of copolymer (A) / curing agent (B) is preferably 60 / 40 or more and 95 / 5 or less. If the mass ratio of copolymer (A) / curing agent (B) is smaller than the above range, the water dispersibility (water solubility or emulsification) of copolymer (A) and curing agent (B) in the bake-curing type electrodeposition liquid is reduced, and liquid separation or sedimentation is likely to occur. In addition, the hardness of the electrodeposition coating film is likely to be insufficient. Furthermore, the production cost is also significantly increased. If the mass ratio of copolymer (A) / curing agent (B) is greater than the above range, it becomes difficult to obtain sufficient coating film performance (chemical resistance, coating film hardness).
[0012] The total content of the copolymer (A) and the curing agent (B) in the bake-curable electrodeposition liquid is preferably 8% by mass or more and 12% by mass or less. Within the above range, good handling properties and electrodeposition coating efficiency are easily obtained.
[0013] (Viscosity of bake-hardening electrodeposition liquid) The viscosity of the bake-curable electrodeposition liquid of the present invention, measured at 100 rpm using a Brookfield viscometer equipped with an L-type rotor and a low-viscosity adapter, is preferably 1.50 mPa s or more and 2.70 mPa s or less. Within the above range, good handleability and electrodeposition coating efficiency are easily obtained.
[0014] [Stability of bake-hardening electrodeposition solution] It is preferable that the bake-hardening electrodeposition solution does not cause settling or separation during storage. For example, when the bake-hardening electrodeposition liquid is placed in a transparent glass container and allowed to stand for 48 hours, it is preferred that no settling or separation be detected visually.
[0015] [Copolymer (A)] The bake-curable electrodeposition solution of the present invention can be used for electrodeposition onto a 3D printer metal object by either anionic electrodeposition or cationic electrodeposition by changing the type of functional group contained in the copolymer (A).
[0016] In the case of anionic electrodeposition of the bake-curable electrodeposition liquid of the present invention, the copolymer (A) is preferably an anionic resin having a carboxyl group. In order to obtain such a copolymer (A) having a carboxyl group, it is preferable to synthesize the copolymer (A) using, for example, a monomer (a) having a polymerizable carbon-carbon unsaturated bond group and a carboxyl group. Specific examples of the carbon-carbon unsaturated bond group include a vinyl group, an allyl group, a (meth)acrylic group, and an αβ-unsaturated carbonyl group, and these may be polymerized alone or two or more kinds may be copolymerized.
[0017] In the case of cationic electrodeposition of the bake-curable electrodeposition liquid of the present invention, the copolymer (A) is preferably a cationic resin having a tertiary amino group. In order to obtain such a copolymer (A) having a tertiary amino group, for example, it is preferable to synthesize the copolymer (A) using a monomer (a) having a polymerizable carbon-carbon unsaturated bond group and a tertiary amino group.
[0018] The copolymer (A) is a copolymer of monomers (a), (b) and (c), and has hydroxyl groups and carboxyl groups or tertiary amino groups, and is water-soluble or water-dispersible. The main skeleton of the copolymer (A) is mainly formed by (co)polymerization of polymerizable carbon-carbon unsaturated bond groups, such as polymerizable carbon-carbon double bonds or triple bonds, contained in the monomers (a), (b), and (c).
[0019] The copolymer (A) has a carboxyl group or a tertiary amino group, and thus can exhibit good water solubility or water dispersibility in the solvent (C), which is an aqueous solvent. The copolymer (A) has a hydroxyl group, and thus can form a crosslink with the curing agent (B), thereby improving the corrosion resistance (weather resistance, chemical resistance), hardness, and the like. The crosslinking reaction between the copolymer (A) and the curing agent (B) proceeds, for example, between the hydroxyl groups of the copolymer (A) and the isocyanate groups or blocked isocyanate groups and / or alkylated methylol groups of the curing agent (B) in the bake curing process of the electrodeposition coating film.
[0020] When the copolymer (A) has a tertiary amino group, the tertiary amino group may have two alkyl groups having 1 to 4 carbon atoms.
[0021] When the copolymer (A) has a carboxyl group, the acid value is preferably from 30 to 70 mgKOH / g. When the copolymer (A) has a tertiary amino group, the amine value is preferably from 18 to 40 mgKOH / g. If the acid value or amine value is within this range, a good bake-curable electrodeposition liquid can be prepared. If the acid value or amine value is below the above range, it is difficult to obtain sufficient water dispersibility, and if it is higher than the above range, the water resistance is easily reduced, making it difficult to obtain sufficient coating performance.
[0022] The glass transition temperature (Tg) of the copolymer (A) is preferably 20 to 40° C., more preferably 25 to 35° C. If it is lower than the above range, the electrodeposition coating film tends to flow easily in the bake hardening step of the electrodeposition coating film, so that the electrodeposition coating film tends to become thin, whereas if it is higher than the above range, the fluidity of the electrodeposition coating film is too low, so that the smoothness of the electrodeposition coating film surface tends to be inferior.
[0023] (How to calculate Tg value) In the present invention, the Tg value of the copolymer (A) can be calculated from the Tg values of the homopolymers of the monomers (a), (b), and (c) used according to the following formula: 1 / Tg A =1 / Tg1×Wt1+1 / Tg2×Wt2+···+1 / Tg n ×Wt n Tg A : Tg of copolymer (A) [absolute temperature (K)] Tg1, Tg2, ...Tg n : Tg of homopolymer of each monomer [absolute temperature (K)] Wt1, Wt2, ... Wt n : Mass fraction of each monomer relative to the total amount As the Tg of each homopolymer of each monomer, for example, the value described in "Introduction to Synthetic Resins for Paints" (Polymer Publishing Association, Kyozo Kitaoka, New Polymer Library 7) can be used. When two or more types of copolymers (A) are used, the Tg and mass fraction of each copolymer (A) can be substituted into the above formula for calculation.
[0024] The solubility parameter (SP) value of copolymer (A) is 10.50 to 11.50 (cal / cm 3 ) 0.5When the solubility parameter value is within the above range, the copolymer (A) has appropriate hydrophilicity and is easily excellent in water solubility or water dispersibility, so that the bake-curable electrodeposition solution is less likely to sediment and separate. If the SP value is lower than the above range, the hydrophobicity tends to be too high, whereas if it is higher than the above range, the hydrophilicity tends to be too high, so that the bake-hardenable electrodeposition solution is prone to sedimentation.
[0025] (How to calculate SP value) In the present invention, the SP value of copolymer (A) can be calculated from the SP values of monomers (a), (b), and (c) used according to the following formula (Fedors' solubility parameter calculation formula: RF Fedors, Polym. Eng. Sci., 14[2]147(1974)). First, the SP value of each monomer is calculated using the values described in, for example, "Practical Edition of Plastic Coating Technology Comprehensive Guide" (edited by Materials Technology Research Association, pages 97-138). δ = (ΔE / V) 1 / 2 =(ΣΔe i / ΣΔv i ) 1 / 2 δ: SP value of each monomer [(cal / cm 3 ) 0.5 ] ΔE: Cohesive energy [cal / mol] V: Molar volume [cm 3 / mol] Δe i : Evaporation energy of an atom or group of atoms [cal / mol] Δv i : Molar volume of an atom or group of atoms [cm 3 / mol] Next, the SP value of the copolymer (A) is calculated by the following formula. SP A = δ1 × Wt1 + δ2 × Wt2 + + δ n ×Wt n SP A : SP value of copolymer (A) [(cal / cm 3 ) 0.5 ] δ1, δ2, δ n : Calculated δ[(cal / cm 3 ) 0.5 ] Wt1, Wt2, ... Wt n : Mass fraction of each monomer relative to the total amount When two or more types of copolymers (A) are used, the SP of each copolymer (A) is A and the mass fraction can be calculated by applying the above formula.
[0026] The mass fraction of the structural portion derived from the monomer (a) in the copolymer (A) is preferably 2 to 15 mass%, more preferably 4 to 10 mass%. If it is lower than the above range, the water solubility of the copolymer (A) decreases, and the particle size of the emulsion in the bake-curable electrodeposition solution becomes too large, which tends to cause sedimentation and separation. If it is higher than the above range, the coating film performance such as water resistance to boiling water after baking tends to decrease.
[0027] The mass fraction of the structural portion derived from the monomer (b) in the copolymer (A) is preferably 2 to 15 mass%, more preferably 4 to 10 mass%. If it is lower than the above range, the crosslinking reaction between the copolymer (A) and the curing agent (B) tends to proceed less easily in the bake-hardening step of the electrodeposition coating film, whereas if it is higher than the above range, the hydrophilicity tends to be too high, and the bake-hardening electrodeposition liquid tends to sediment and separate.
[0028] In the bake-hardening electrodeposition liquid, the content of the magnetic powder (D) is preferably 40 to 170 phr, more preferably 50 to 160 phr, based on the total amount of the copolymer (A) and the hardener (B). The content of the magnetic powder (D) is preferably from 2 to 6 mass %, more preferably from 3 to 5 mass %, in the total amount of the bake hardenable electrodeposition liquid. When the content of the magnetic powder (D) is within the above range, the bake-hardenable electrodeposition liquid is likely to have good handleability, electrodeposition coating efficiency, and magnetic function, and the formed electrodeposition coating can also have excellent magnetic function.
[0029] The content of the pigment (E) in the bake-curable electrodeposition liquid is preferably 0.1 to 1 mass %, more preferably 0.3 to 0.7 mass %. If the content is lower than the above range, the color of the coating film is pale and the coloring effect is not easily achieved, whereas if the content is higher than the above range, the coating film performance is easily reduced. In addition, the bake-hardenable electrodeposition liquid may be prepared by using a pigment liquid containing the pigment (E). In this case, the content of the pigment (E) is not the content of the pigment liquid but the content of the pigment (E) component.
[0030] (Method of synthesizing copolymer (A)) The copolymer (A) is preferably synthesized by synthesizing the monomers (a), (b) and (c) in various water-soluble solvents, and various polymerization initiators can be used as necessary. Specific examples of the water-soluble solvent include water, alcohols, ethylene glycol ethers, and propylene glycol ethers. One or a combination of two or more selected from this group can be used, but the water-soluble solvent is not limited to these. Among the above, isopropanol, ethylene glycol mono-n-butyl ether, propylene glycol monomethyl ether, etc. are preferably used.
[0031] As the polymerization initiator, a radical initiator is preferably used. Specific examples of the radical initiator include dihalogen compounds, azo compounds, organic peroxides, redox initiators, etc., and one or more types selected from this group can be used in combination, but are not limited to these. Of the above, azo compounds are preferably used, and among the azo compounds, 2,2'-azobisisobutyronitrile, 2,2'-azobisiso(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile) are preferably used.
[0032] [Monomer (a)] The monomer (a) is a monomer having a polymerizable carbon-carbon unsaturated bond group and a carboxyl group or a tertiary amino group.
[0033] Specific examples of the monomer (a) having a polymerizable carbon-carbon unsaturated bond group and a carboxyl group include acrylic acid, α-chloroacrylic acid, methacrylic acid, itaconic acid, maleic anhydride, maleic acid, fumaric acid, crotonic acid, citraconic acid, mesaconic acid, etc., and one or more selected from the group consisting of these may be used in combination. Among the above, acrylic acid and methacrylic acid are preferred in that they easily undergo copolymerization reaction with monomer (b) and monomer (c).
[0034] When the monomer (a) has a tertiary amino group, the tertiary amino group may have two alkyl groups having 1 to 4 carbon atoms.
[0035] Specific examples of the monomer (a) having a polymerizable carbon-carbon unsaturated bond group and a tertiary amino group include 2-(dimethylamino)ethyl acrylate, 2-(diethylamino)ethyl acrylate, 2-(dimethylamino)ethyl methacrylate, and 2-(diethylamino)ethyl methacrylate, which are compounds that increase the water solubility of the copolymer and facilitate the preparation of an electrodeposition liquid emulsion. One or a combination of two or more selected from the group consisting of these can be used.
[0036] [Monomer (b)] The monomer (b) is a monomer having a polymerizable carbon-carbon unsaturated bond group and a hydroxyl group. Specific examples of monomer (b) include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, diethylene glycol monoacrylate, cyclohexanedimethanol monoacrylate, and cyclohexanedimethanol monomethacrylate. One or a combination of two or more selected from the group consisting of these may be used. Among the above, it is preferable to use one or a combination of two or more selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, and 4-hydroxybutyl methacrylate, in view of their high reactivity with the curing agent (B).
[0037] [Monomer (c)] The monomer (c) is a monomer having a polymerizable carbon-carbon unsaturated bond group, other than the monomer (a) and the monomer (b).
[0038] Specific examples of the monomer (c) include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, normal butyl acrylate, normal butyl methacrylate, normal hexyl acrylate, normal hexyl methacrylate, normal heptyl acrylate, normal heptyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, normal lauryl acrylate, lauryl methacrylate, stearyl acrylate, Examples of the copolymer include acrylate, stearyl methacrylate, styrene, α-methylstyrene, α-chlorostyrene, vinyl toluene, acrylonitrile, vinyl acetate, acrylamide, N-methoxymethylacrylamide, N-ethoxymethylacrylamide, N-normal butoxymethylacrylamide, N-isobutoxymethylacrylamide, N-methoxymethylmethacrylamide, N-ethoxymethylmethacrylamide, N-normal butoxymethylmethacrylamide, and N-isobutoxymethylmethacrylamide. One or a combination of two or more selected from the group consisting of these copolymers may be used. Among the above, it is preferable to use methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, normal butyl acrylate, normal butyl methacrylate, normal hexyl acrylate, normal hexyl methacrylate, normal heptyl acrylate, normal heptyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, styrene, acrylonitrile, and acrylamide in terms of ease of availability of raw materials.
[0039] [Hardening agent (B)] The curing agent (B) is a compound that reacts with the copolymer (A) to crosslink and form a cured product. Specific examples of the curing agent (B) include amino resins and / or isocyanate resins.
[0040] (Amino Resin) Amino resin is a general term for resins obtained by a condensation reaction between a compound containing an amino group or an amide group, such as urea or melamine, and an aldehyde. Examples of the amino resin include melamine resin, guanamine resin, benzoguanamine resin, urea resin, thiourea resin, aniline-formaldehyde resin, etc., and one or more types selected from the group consisting of these can be used in combination. As the aldehyde, for example, formaldehyde is mainly used, and a methylol compound (hydroxymethyl compound) is produced by reacting an amino group or an amide group with formaldehyde, whereby formaldehyde is added to a nitrogen atom. For example, some or more of the -NH2 groups contained therein are methylolated to generate methylol groups such as -NH-CH2-OH or -N(CH2-OH)2, and some or more of the methylol groups are further converted to alkylated methylol groups to generate -NH-CH2-OR, -N(CH2-OR)2 or -N(CH2-OH)(CH2-OR). The amino resin preferably has two or more alkylated methylol groups in one molecule. From the viewpoint of ease of reaction with the copolymer (A), the amino resin is preferably a melamine resin, and more preferably a melamine resin having alkylated methylol groups in which at least a portion of the methylol groups is alkylated with a lower alcohol.
[0041] As the lower alcohol, it is preferable to use one or a combination of two or more selected from the group consisting of methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and the like. That is, the above alkylated methylol group is preferably one or a combination of two or more selected from the group consisting of a methylated methylol group, an ethylated methylol group, an n-propylated methylol group, an isopropylated methylol group, an n-butylated methylol group, an isobutylated methylol group, and the like.
[0042] (Isocyanate resin) An isocyanate resin is a resin that has two or more isocyanate groups in one molecule. Isocyanate resins also include blocked isocyanate resins in which the isocyanate groups are blocked with various blocking agents. Specific examples of the isocyanate resin include 3,5-dimethylpyrazole blocked hexamethylene diisocyanate trimer, and one or more types selected from the group consisting of these may be used.
[0043] A blocked isocyanate resin is an isocyanate resin in which the isocyanate group is blocked (capped, protected) with a blocking agent. The blocked isocyanate resin can be heated to dissociate the blocking agent, regenerate the isocyanate group, and then react the isocyanate group.
[0044] Examples of the isocyanate resin include aromatic isocyanate resins, aliphatic isocyanate resins, alicyclic isocyanate resins, biuret forms thereof, isocyanurate forms thereof, and adducts which are reaction products of trimethylolpropane and the above-mentioned isocyanate compounds. Specific examples of the isocyanate resin include tolylene diisocyanate, xylylene diisocyanate, phenylene diisocyanate, diphenylmethane-2,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, bis(isocyanatomethyl)cyclohexane, tetramethylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate. Among the above, tetramethylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate are preferred.
[0045] Examples of the blocking agent include lactam compounds such as ε-caprolactam and γ-butyrolactam; oxime compounds such as methyl ethyl ketoxime and cyclohexanone oxime; phenol compounds such as phenol, para-t-butylphenol and cresol; pyrazole compounds such as 3,5-dimethylpyrazole and 3,5-diisopropylpyrazole; active methylene compounds such as diethyl malonate, ethyl acetoacetate and acetylacetone; aliphatic alcohols such as n-butanol and 2-ethylhexanol; aromatic alkyl alcohols such as phenyl carbinol and methylphenyl carbinol; and ether alcohol compounds such as ethylene glycol monobutyl ether and diethylene glycol monoethyl ether.
[0046] Among the above, lactam compounds, oxime compounds, and pyrazole compounds are preferred, and more preferred are ε-caprolactam, γ-butyrolactam, methyl ethyl ketoxime, cyclohexanone oxime, and 3,5-dimethylpyrazole.
[0047] Solvent The solvent (C) is a water-based solvent capable of forming an aqueous solution or emulsion together with the copolymer (A) and the curing agent (B). The solvent (C) is an aqueous solvent, and preferably contains an aqueous organic solvent and water. The aqueous organic solvent may be one type of aqueous organic solvent, or a mixed solvent consisting of a plurality of types of aqueous organic solvents. The content of the aqueous organic solvent in the bake-curable electrodeposition solution is preferably 0.1% by mass or more and 5% by mass or less, and more preferably 2.0% by mass or more and 4.0% by mass or less. If the content is lower than the above range, the film formation state during electrodeposition is inferior, and the surface shape of the electrodeposition coating is likely to become uneven and the surface smoothness is likely to be inferior. If the content is higher than the above range, the thickness of the electrodeposition coating is likely to vary greatly.
[0048] (water) The water used is preferably deionized water. When water having a high ion content is used, gas is likely to be generated during electrodeposition coating due to miscellaneous ions mixed in the bake-hardening type electrodeposition liquid.
[0049] (Water-based organic solvent) The aqueous organic solvent is preferably one or a combination of two or more selected from the group consisting of alcohols, ethylene glycol ethers, and propylene glycol ethers. Alcohols, ethylene glycol ethers, and propylene glycol ethers are excellent in plasticizing the copolymer (A) and the hardener (B), in solubility, and in affinity with water. In addition, alcohols, ethylene glycol ethers, and propylene glycol ethers It can also be used as a solvent when synthesizing the copolymer (A), and it is preferable that the solvent when synthesizing the copolymer (A) and the solvent (C) contain a common solvent. If the two solvents have high commonality, the reaction solution used in synthesizing the copolymer (A) can be blended as is in the bake-curable electrodeposition solution.
[0050] Specific examples of alcohols include methanol, ethanol, normal propanol, isopropanol, normal butanol, isobutanol, normal hexyl alcohol, 2-ethylhexyl alcohol, benzyl alcohol, and the like. One or a combination of two or more selected from the group consisting of these may be used, but is not limited to these.
[0051] Specific examples of ethylene glycol ethers include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-normal propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono-normal butyl ether, ethylene glycol monoisobutyl ether, ethylene glycol mono-tertiary butyl ether, ethylene glycol mono-normal hexyl ether, ethylene glycol mono-normal octyl ether, ethylene glycol mono-2-ethylhexyl ether, and the like. One or a combination of two or more selected from the group consisting of these may be used, but the present invention is not limited to these.
[0052] Specific examples of propylene glycol ethers include propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-normal propyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-normal butyl ether, propylene glycol monoisobutyl ether, propylene glycol mono-tertiary butyl ether, propylene glycol mono-normal hexyl ether, propylene glycol mono-normal octyl ether, and propylene glycol mono-2-ethylhexyl ether. One or a combination of two or more selected from the group consisting of these propylene glycol ethers may be used, but the present invention is not limited to these.
[0053] The solvent (C) preferably contains a mixture of isopropanol and ethylene glycol mono-normal butyl ether in a mass ratio of 15 / 4 to 4 / 15. The solvent used in synthesizing the copolymer (A) must have an excellent balance of reaction temperature, reflux temperature, boiling point of the solvent, and affinity with water, and a mixture containing isopropanol and ethylene glycol mono-normal butyl ether in a mass ratio of 15 / 4 to 4 / 15 is preferably used. Therefore, if the solvent (C) contained in the bake-hardenable electrodeposition liquid has a composition similar to that of the solvent used in synthesizing the copolymer (A), the reaction liquid used in synthesizing the copolymer (A) can be blended directly into the bake-hardenable electrodeposition liquid.
[0054] [Magnetic powder (D)] The magnetic powder (D) is a powdered magnetic material. There are two types of magnetic substances: hard magnetic substances, which become permanent magnets once a strong magnetic field is applied, and soft magnetic substances, which become magnets when they come into contact with a magnetic field (magnet) and return to their original state and lose their magnetism when the magnetic field is removed. When the 3D printed metal molded product with the baked-hardened electrodeposition coating film of the present invention is used as an actuator, it is preferable to use a soft magnetic substance rather than a hard magnetic substance for the magnetic substance powder (D).
[0055] The shape of the magnetic powder (D) is not particularly limited, but a spherical shape is preferred in order to suppress thickening of the bake-hardenable electrodeposition liquid. Although there is no particular limitation on the particle size of the magnetic powder (D), the maximum particle size is preferably 10 μm or less. Here, for example, when the 10 μm sieve residue is 0.1% or less, the maximum particle size can be substantially considered to be 10 μm or less. When the particle size of the magnetic powder (D) is within the above range, good viscosity, throwing power, and other good coatability are easily obtained.
[0056] Representative magnetic materials include iron oxide, chromium oxide, cobalt, ferrite, and non-oxidized metal magnetic materials. Among the above, ferrite is preferably used since it is easily available and inexpensive.
[0057] The magnetic material is a magnetic oxide containing iron oxide as a main component, and may further contain elements other than iron and oxygen. There are two types of ferrite: hard ferrite, which becomes a permanent magnet once a strong magnetic field is applied, and soft ferrite, which becomes a magnet when it comes into contact with a magnetic field (magnet) and returns to its original state and loses its magnetism when the magnetic field is removed. Either hard ferrite or soft ferrite can be used for the ferrite powder (D) of the present invention.
[0058] Pigment A water-dispersible pigment can be used for the pigment (E). If the pigment is water-dispersible, it will migrate in a uniform state to the surface of the 3D printed metal object together with the resin components such as the copolymer (A) and the hardener (B) during the electrodeposition process, allowing the electrodeposition film to exhibit a uniform color development.
[0059] [Neutralizer (F)] As the neutralizing agent (F), organic amines and carboxylic acids can be used. The organic amines can neutralize the carboxyl groups of the copolymer (A) to increase the emulsifiability or water solubility of the copolymer (A), thereby increasing the dispersibility of the copolymer (A). The carboxylic acids can neutralize the tertiary amino groups in the copolymer (A) to increase the emulsifiability or water solubility of the copolymer (A) and thereby increase the dispersibility of the copolymer (A).
[0060] The organic amines include alkylamines, alkanolamines, alkylenepolyamines, alkyleneimines, cyclic amines, etc., and may be used alone or in combination of two or more selected from these groups, but are not limited thereto. Among the above, it is more preferable to use alkanolamines.
[0061] Specific examples of alkylamines include monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, triethylamine, monoisopropylamine, diisopropylamine, triisopropylamine, monobutylamine, dibutylamine, tributylamine, and the like. One or a combination of two or more selected from this group can be used, but is not limited to these.
[0062] Specific examples of alkanolamines include monoethanolamine, diethanolamine, triethanolamine, mono(2-hydroxypropyl)amine, di(2-hydroxypropyl)amine, tri(2-hydroxypropyl)amine, dimethylaminoethanol, diethylaminoethanol, and the like. One or a combination of two or more selected from this group can be used, but is not limited to these.
[0063] Specific examples of alkylene polyamines include ethylene diamine, propylene diamine, diethylene triamine, triethylene tetramine, etc., and one or a combination of two or more selected from this group can be used, but is not limited to these.
[0064] Specific examples of alkyleneimines include ethyleneimine, propyleneimine, and the like. One or a combination of two or more selected from this group can be used, but the alkyleneimines are not limited thereto. Specific examples of cyclic amines include piperazine, morpholine, pyrazine, pyridine, etc., and one or more selected from this group may be used in combination, but is not limited to these.
[0065] Examples of the carboxylic acid include organic acids such as formic acid, acetic acid, propionic acid, lactic acid, butyric acid, 2-ethylbutanoic acid, and octylic acid, as well as sulfuric acid and phosphoric acid. Of these, acetic acid and lactic acid are preferably used.
[0066] When the neutralizing agent (F) is contained in the bake-curable electrodeposition liquid, the molar ratio of amino groups of the neutralizing agent (F) to carboxyl groups of the copolymer (A), or the molar ratio of carboxyl groups of the neutralizing agent (F) to tertiary amino groups of the copolymer (A) is preferably 0.3 to 0.9, and more preferably 0.4 to 0.7. If the molar ratio is lower than the above range, the effect of increasing the water solubility or emulsifiability of the copolymer (A) is likely to be insufficient, whereas if the molar ratio is higher than the above range, the time required for the electrodeposition coating step is likely to be long.
[0067] [3D printed metal model] The 3D printer metal object onto which the bake-hardenable electrodeposition liquid of the present invention is electrodeposited is a metal object having one or more types of structural features selected from the group consisting of groove-shaped recesses, cylindrical recesses, polygonal tubular recesses, and lattice structures, and has a complex structure that is difficult to mold by conventional casting. Specific examples of such metal shaped products include metal machines, general metal tools, metal ornaments, and the like. The production of metal objects using a 3D printer does not require pouring molten metal into a mold, and does not require die cutting, so it is possible to produce metal objects with groove-shaped recesses, cylindrical recesses, polygonal tubular recesses, lattice structures, or other intricate 3D structures. However, such 3D printed metal objects have the disadvantage that their complex shapes make it difficult to paint them effectively using conventional non-electrochemical coating.
[0068] The depth and width of the groove-like recesses, cylindrical recesses, and polygonal tubular recesses are not particularly limited, but for example, the depth is preferably 25 mm or less, the width is 0.2 mm or more, and the depth / width ratio is preferably 1.0 to 125, and more preferably the depth is 15 mm or less, the width is 2 mm or more, and the depth / width ratio is 2 to 25. Within the above ranges, the bake-hardenable electrodeposition liquid of the present invention can be easily electrodeposited with good throwing power. The lower limit of the depth is preferably substantially 1 mm or more, and more preferably 2 mm or more, from the viewpoint of clearly maintaining the recesses even after painting. Considering the above-mentioned depth and depth / width ratio, the upper limit of the width is preferably substantially 20 mm or less, and more preferably 15 mm or less. The cylindrical recess may be a regular cylinder, an elliptical cylinder, or a bale-shaped cylinder, and the polygonal cylindrical recess may be a regular polygonal cylinder, a scalene polygonal cylinder, or a rounded polygonal cylinder. The width of the recess is the width of the groove in the case of a groove-shaped recess, the shortest diameter in the case of a cylindrical recess, and the diameter of the inscribed circle of the polygon in the case of a polygonal cylindrical recess. A plurality of groove-shaped recesses, cylindrical recesses, and polygonal tubular recesses may be geometrically arranged in 3D to form a cell structure. For example, a plurality of hexagonal tubular recesses may form a honeycomb structure.
[0069] A lattice structure is a functional structure in which links that connect vertices (points) are geometrically arranged in 3D (see JIS B9441:2020 Additive Manufacturing (AM) - Terminology and Basic Concepts), and three-dimensional objects are created by arranging branched lattices periodically. There are no particular limitations on the shape or thickness of the links of the lattice structure, but the spacing between the links is preferably 0.5 mm or more in order to allow the bake-hardening electrodeposition liquid to pass through. In the present invention, for example, a truss structure is considered to be a type of lattice structure in which links connecting vertices (points) form triangles.
[0070] For objects with such complex structures, conventional non-electrochemical coating often requires the use of a low-viscosity coating solution with a low solids concentration, resulting in a very thin or uneven coating film, or multiple coating and drying steps must be repeated to create multiple layers to obtain a thick coating film.
[0071] There are no particular limitations on the type of metal that may be used to construct a 3D printer metal object, but examples include aluminum, pure iron, stainless steel, copper, titanium, nickel alloys, etc., and the object may contain one or more types selected from the group consisting of these.
[0072] (How to create metal objects using a 3D printer) The 3D printed metal model may be produced by a variety of 3D printers, for example by powder bed fusion. In powder bed fusion, a powder of a metal (eg, pure iron, stainless steel, copper, titanium, nickel alloys, etc.) is first laid down on a build plate. Then, a laser beam or an electron beam is irradiated to selectively melt and bond the metal powder by heat. The build plate is then lowered one build size and the metal powder is again laid down and selectively melted and bonded in the same manner. By repeating the above steps, it is possible to create 3D printed metal objects with complex shapes. The surface of the completed 3D printer metal model is rough, so it may be polished as necessary by sandblasting, buffing, applying anti-rust oil, etc. In addition, anti-rust oil may be applied to the surface of an iron-based 3D printer metal model to prevent rust. However, it is preferable to remove the anti-rust oil before electrodeposition.
[0073] <3D printer metal model with bake-hardened electrocoated coating> The 3D printer metal object having a bake-curable electrodeposition coating film of the present invention is an object produced by electrodeposition coating the surface of the above-mentioned 3D printer metal object with the bake-curable electrodeposition liquid of the present invention, followed by heat curing. The 3D printer metal object of the present invention with a bake-hardened electrodeposition coating has a complex structure and narrow recesses, yet has a bake-hardened electrodeposition coating that has an excellent balance of uniformity, throwing power, high adhesion, and corrosion resistance.
[0074] (Electrodeposition coating thickness) There is no particular limitation on the thickness of the electrodeposition coating, but the bake-curable electrodeposition liquid of the present invention can form an electrodeposition coating having a thickness of, for example, 3 to 60 μm on a 3D printer metal model having a complex structure.
[0075] (Uniformity of electrocoating film) It is preferable that when a bake-hardened electrocoating film is formed on the surface of a 3D printer metal object, the difference in thickness between locations is within ±10 μm when a bake-hardened electrocoating film of approximately 50 μm is formed. For example, when a bake-hardened electrodeposition coating film having a thickness of about 50 μm is formed on a recess having a depth of 1 to 25 mm, a width of 0.2 to 20 mm, and a depth / width ratio of 1.0 to 125, it is preferable that the thickness difference between the bottom and wall portions is within ±10 μm. If the thickness difference is within the above range, the bake-hardenable electrodeposition liquid exhibits excellent throwing power, and excellent smoothness, high adhesion, and corrosion resistance are easily obtained.
[0076] (Electrodeposition coating adhesion) The throwing power of an electrodeposition coating film is the ability of an electrodeposition liquid to electrodeposit a coating film of uniform thickness without defects. For example, when electrocoating a complex structured metal object created by a 3D printer, if there are no areas that are not electrocoated and the thickness of the thinnest and thickest parts is within ±20% of the average thickness, then it can be said to have excellent throwing power.
[0077] (Adhesion of electrocoating film) The adhesion of the bake-hardened electrodeposition coating to a 3D printed metal object is affected by the surface condition of the 3D printed metal object, the composition of the bake-hardened electrodeposition coating, and the application and curing conditions. The adhesion of the bake-cured electrodeposition coating can be evaluated, for example, in accordance with JIS K 5600-5-6 by engraving 10 × 10 = 100 checkerboard-shaped squares in the bake-cured electrodeposition coating of a 3D printer metal object with a bake-cured electrodeposition coating, and then counting the number of squares that did not peel off and the presence or absence of chipping by tape application and peeling operations. It is preferable that none of the 100 squares peel off and there are no chips.
[0078] (Corrosion resistance) 3D printed metal objects with a bake-hardened electrocoat coating have better corrosion resistance than 3D printed metal objects without a bake-hardened electrocoat coating because the bake-hardened electrocoat coating is formed on the surface. However, if the bake-hardened electrocoat coating is uneven or has defects, corrosion will progress and the atomic hydrogen generated will penetrate and accumulate on the surface of the 3D printed metal object. As this gasifies, the surface will rise into a disk-like shape and form a blister (bulge). The corrosion resistance of a 3D printer metal molded object with a bake-hardened electrodeposition coating can be evaluated, for example, according to JIS K 5600-7-1 by making cross cuts in the bake-hardened electrodeposition coating of a 3D printer metal molded object with a bake-hardened electrodeposition coating, spraying neutral salt water, and measuring the width of blisters that have developed after 72 hours. The blister width is preferably less than 3 mm, and more preferably 0 mm, i.e., no blisters are formed.
[0079] (Method for evaluating magnetic materials or method for evaluating characteristics for actuator applications) The bake-curable electrodeposition liquid for use in a three-dimensional printer-made metal object according to the present invention, and the magnetic body formed from a three-dimensional printer-made metal object with a bake-curable electrodeposition coating film, have good soft magnetic properties. Soft magnetism is a property in which a material is strongly magnetized when placed under the influence of a magnetic field, but when the magnetic field is removed, the ability to retain the magnetic force (coercive force) is small and the magnetic permeability is high. The coercive force of a 3D printer metal object having a bake-cured electrodeposition coating film is, for example, preferably 200 A / m, and more preferably 100 A / m or less, when magnetized with an applied magnetic field of 2000 A / m. The 3D printed metal object with the bake-hardened electrodeposition coating film of the present invention, which has low coercive force and excellent soft magnetic properties, is excellent for use as an actuator.
[0080] <Method of forming electrodeposition coating film> The method for forming an electrodeposition coating of the present invention is a method for forming an electrodeposition coating on the surface of a metal object printed by a three-dimensional printer, using the bake-curable electrodeposition liquid of the present invention. The method for forming an electrodeposition coating film of the present invention can include the following steps (1) to (7) in this order. (1) A process for degreasing the surface of a 3D printed metal object; (2) A water washing process for the surface of the 3D printer metal model; (3) A step of immersing a 3D printer metal object in the bake-hardening electrodeposition liquid; (4) A process for removing air bubbles from the surface of a 3D printed metal object; (5) A process for forming an electrocoating film on the surface of a 3D printed metal object; (6) Rinse and drain the electrocoated coating. (7) Bake hardening process of the electrocoating film;
[0081] The details of each step are as follows. (1) A process for degreasing the surface of the 3D printer metal model The surface of a 3D printer metal object may be coated with oil to prevent rust. In order to form a highly adhesive electrocoating, it is preferable to remove this oil with an alkaline degreasing solution or the like. The 3D printer metal model is preferably immersed in a degreasing solution at a temperature of preferably 40 to 60° C., more preferably 45 to 55° C., for preferably 1 to 5 minutes, more preferably 2 to 4 minutes. When the 3D printer metal object has a particularly complicated structure, it may be further immersed in a plurality of degreasing solutions having different compositions.
[0082] (2) A water washing process for the surface of 3D printed metal objects After the 3D printer metal object with its surface degreased has been removed from the degreasing solution, it is preferable to rinse it by immersing it in or spraying it with deionized water at room temperature in a circulating water washing tank for preferably 30 to 90 seconds, and more preferably 45 to 75 seconds.
[0083] (3) Immersing the 3D printed metal object in a bake-hardening electrodeposition solution The bake-hardenable electrodeposition liquid into which the 3D printer metal object is immersed is preferably kept at a temperature of 18 to 28°C, and more preferably kept at a constant temperature of 20 to 25°C, in order to stabilize the viscosity. It is preferable that a 3D printer metal object that is to be immersed in a bake-hardening electrodeposition liquid be washed with water and immersed in a state in which the surface is still wet, in order to enhance affinity of the bake-hardening electrodeposition liquid to the surface. Furthermore, during immersion, in order to improve compatibility of the bake-hardenable electrodeposition liquid with the surface of the 3D printer metal object, it is preferable to immerse the 3D printer metal object while stirring the bake-hardenable electrodeposition liquid 1 in the electrodeposition tank.
[0084] (4) Removal of air bubbles from the surface of 3D printed metal objects If air bubbles are present on the surface of a 3D printed metal object immersed in a bake-hardening electrodeposition liquid, it is difficult for the bake-hardening electrodeposition liquid to be electrodeposited into the voided areas, so it is preferable to remove the air bubbles. To remove air bubbles, it is preferable to agitate the bake-hardening electrodeposition liquid in the electrodeposition tank while rocking the immersed 3D printer metal object up and down, preferably for 20 to 40 seconds, and more preferably for 25 to 35 seconds. By removing air bubbles, the entire surface of the 3D printed metal object can be evenly coated with the bake-hardening electrodeposition liquid.
[0085] (5) Electrodeposition coating process on the surface of 3D printed metal objects When the bake-hardenable electrodeposition solution of the present invention is used for anion electrodeposition, a voltage is applied to the workpiece as the anode and the electrode as the cathode, and when it is used for cationic electrodeposition, a voltage is applied to the workpiece as the cathode and the electrode as the anode. There is no particular restriction on the electrode on the side opposite to the object to be coated, but it is preferable to use a stainless steel plate, specifically SUS304, SUS316, etc. as the stainless steel.
[0086] In order to obtain a uniform electrodeposition coating in a short time, it is preferable to stop stirring the bake-hardening electrodeposition liquid and the up-and-down movement of the metal model printed on the 3D printer when the voltage is applied. Furthermore, after the voltage application is completed, the three-dimensional printed metal object 1 is preferably left to stand in the bake-hardening electrodeposition liquid 1 for preferably 5 to 15 seconds, and more preferably 8 to 12 seconds, thereby enhancing the compatibility of the formed electrodeposition coating film with the surface of the three-dimensional printed metal object.
[0087] The bake-hardenable electrodeposition solution of the present invention can be used for electrodeposition by either a constant current method or a constant voltage method. In general, when an electrodeposition coating is formed by a constant voltage method, as the electrodeposition coating resistance increases due to the growth of the thickness of the electrodeposition coating, the current value decreases or slows down, and the formation rate of the electrodeposition coating decreases. When forming an electrodeposition coating by a constant current method, the rate of formation of the electrodeposition coating can be maintained by applying a relatively high voltage as the resistance of the electrodeposition coating increases, thereby maintaining the current value. However, when using the constant current method, the thickness of the electrocoating film formed is determined by the integrated value of the current density and the time the current is passed through, and since it is difficult to calculate or measure the surface area of complex shaped 3D printed metal objects, it is difficult to obtain the desired film thickness. Therefore, it is preferable that the bake-hardenable electrodeposition solution of the present invention is used to form an electrodeposition coating film by a constant voltage method.
[0088] (Constant voltage application conditions) When electrodeposition coating is performed by the constant voltage method, the voltage is preferably 80 to 200 volts and the current application time is preferably 1 to 3 minutes.
[0089] (Constant current application conditions) When using the constant current method for electrodeposition coating, the current density is 0.02 to 0.60 A / dm 2 The current application time is preferably 1 to 3 minutes.
[0090] (6) Rinse and drain the electrocoating film After the produced 3D printer metal object with an electrodeposition coating is removed from the bake-hardening electrodeposition solution, it is preferably rinsed by immersing it in deionized water in a circulating water washing tank for preferably 30 to 90 seconds, and more preferably 45 to 75 seconds. After being removed from the deionized water, the coating is drained at room temperature of 20 to 30°C, preferably for 3 to 7 minutes, more preferably for 4 to 6 minutes, and then water droplets on the coating surface are removed with an air blower or the like to dry the coating surface.
[0091] (7) Bake hardening process of electrocoating The 3D printed metal object with the electrocoating film can be heated and baked in a hot air convection oven, far-infrared heater oven, etc., and hardened. The heating temperature is preferably from 160 to 200°C, and more preferably from 170 to 190°C. The heating time is preferably from 15 to 60 minutes, more preferably from 20 to 45 minutes. EXAMPLES
[0092] The main raw materials and materials used in the examples of the present invention are as follows. <Ingredients> Monomer (a1): Acrylic acid Monomer (a2): 2-(diethylamino)ethyl methacrylate Monomer (b1): 2-hydroxyethyl acrylate Monomer (b2): 2-hydroxyethyl methacrylate Monomer (c1): styrene Monomer (c2): Ethyl acrylate Monomer (C3): n-butyl acrylate Monomer (c4): 2-ethylhexyl acrylate Monomer (C5): Methyl methacrylate
[0093] Melamine resin 1: Cymel 285-100 manufactured by Allnex Japan Co., Ltd. A melamine resin in which all of the methylol groups are methylated methylol groups or butylated methylol groups. Melamine resin 2: Cymel 1125 manufactured by Allnex Japan Co., Ltd. A melamine resin that has imino groups and some of the methylol groups are methylated methylol groups. Isocyanate resin 1: Trixene BI 7982 manufactured by Lanxess. A solution of 3,5-dimethylpyrazole blocked hexamethylene diisocyanate trimer / propylene glycol monomethyl ether in a mass ratio of 70 / 30.
[0094] Ferrite powder 1: Spherical synthetic magnetite, BL-500, manufactured by Titan Kogyo Co., Ltd. Chemical composition: Fe3O4, specific gravity: 5.0, main component: 97% or more, moisture: 0.5% or less, oil absorption: 28±5g / 100g. 45μm sieve residue: 0.1% or less. Glass beads 1: Glass beads with a diameter of 1.0 mm.
[0095] Fermented lactic acid solution 1: Contains 88% L-lactic acid produced from grains and 12% water. Deionized water: Water generated using ion exchange resin or reverse osmosis (RO) membranes. Conductivity of 1μS / cm or less.
[0096] Degreasing solution 1: A 3% by mass aqueous solution of Fine Cleaner 315E manufactured by Nippon Parkerizing Co., Ltd. Degreasing solution 2: An aqueous solution containing 4% by mass of Epane 420 manufactured by Daiichi Kogyo Seiyaku Co., Ltd. and 6% by mass of butyl cellosolve.
[0097] <Synthesis and Evaluation of Copolymer (A)> [Synthesis Example 1] The following compounds were placed in a 3-liter, four-neck flask equipped with a stirrer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube, and the mixture was heated to 90° C. and refluxed. Isopropanol 15 parts by weight Butyl cellosolve 8.75 parts by mass Separately from the above, a mixed solution of the following compounds was placed in a dropping funnel and added dropwise to the flask over 120 minutes to allow the reaction to proceed. Monomer (a1) 5 parts by mass Monomer (b1) 3 parts by mass Monomer (b2) 12 parts by mass Monomer (c1) 2 parts by mass Monomer (c2) 30 parts by mass Monomer (c3) 5 parts by mass Monomer (c4) 2 parts by mass Monomer (c5) 41 parts by mass Azobisisobutyronitrile 1.2 parts by mass Isopropanol 14 parts by weight Thirty minutes after the completion of the dropwise addition, a mixed solution of the following compounds was further added dropwise to continue the reaction. Azobisisobutyronitrile 0.25 parts by mass Isopropanol 1 part by weight After 30 minutes, a mixed liquid of the following compounds was further added dropwise, and the reaction was continued at 90° C. for an additional 120 minutes to obtain a copolymer (A1) reaction liquid. Azobisisobutyronitrile 0.25 parts by mass Isopropanol 1 part by weight The copolymer (A1) obtained by removing the solvent from the reaction solution had a Tg of 31.7°C and an SP value of 10.56 (cal / cm 3 ) 0.5 It was.
[0098] [Synthesis Examples 2-7] Monomer (a), monomer (b), and monomer (c) were selected according to the description in Table 1, and the same procedure as in Synthesis Example 1 was carried out to obtain reaction solutions of copolymers (A1) to (A7), which were then evaluated in the same manner.
[0099] [Table 1]
[0100] <Preparation of magnetic material dispersed resin liquid> The copolymer (A1) reaction liquid obtained above, melamine resin 1, butyl cellosolve, and dimethylaminoethanol were mixed in the proportions shown in Table 2 in parts by mass, and stirred. Then, while continuing stirring, deionized water in the amount of parts by mass shown in Table 2 was further added and stirred. Furthermore, 1 part by mass of ferrite powder and 1 part by mass of glass beads shown in Table 2 were added and stirred, and dispersed with a Disper disperser at 5,000 rpm for 30 minutes. After the dispersion was completed, the glass beads 1 were removed by filtration through a metal mesh to obtain a ferrite-dispersed resin liquid.
[0101] [Table 2]
[0102] <Creating 3D printer metal objects> Three-dimensional printed aluminum metal objects 1 to 5 having the groove-like recesses shown in FIG. 1 and three-dimensional printed metal object 6 made of low-carbon steel S20C, which is a truss structure shown in FIG. 3, were produced using a Lumex Advance-25 laser powder bed type three-dimensional printer manufactured by Matsuura Machinery Works, Ltd., according to the procedure described below. 3D printer metal model 1 (groove-shaped recess: depth 20 mm, width 4 mm, depth / width ratio 5) 3D printer metal model 2 (groove-shaped recess: depth 1mm, width 1mm, depth / width ratio 1) 3D printer metal model 3 (groove-shaped recess: depth 25 mm, width 1.0 mm, depth / width ratio 25) 3D printer metal model 4 (groove-shaped recess: depth 25 mm, width 0.5 mm, depth / width ratio 50) 3D printer metal model 5 (groove-shaped recess: depth 2 mm, width 0.2 mm, depth / width ratio 10) 3D printer metal model 6 (truss structure: vertex distance 3.0mm, cylindrical link diameter 1.0mm)
[0103] <Preparation and evaluation of bake-hardening electrodeposition solution> [Example 1] (Preparation of bake-hardening electrodeposition solution 1) The copolymer (A2) reaction liquid obtained above, melamine resin 1, and dimethylaminoethanol as a neutralizing agent (F) were mixed in the following ratio and stirred. Copolymer (A2) reaction solution 3.35 parts by mass Melamine resin 1 1.00 parts by weight Dimethylaminoethanol 0.12 parts by mass Next, the ferrite dispersion resin liquid prepared above was added in the amount shown below and further stirred, and then the deionized water in the amount shown below was added and stirred to obtain a bake-curable electrodeposition liquid 1, which was then subjected to various evaluations. Ferrite dispersion resin liquid 8.47 parts by mass Deionized water 87.06 parts by weight The composition of the bake-curable electrodeposition solution 1, including the components contained in the copolymer (A1) reaction solution and the ferrite-dispersed resin solution, is shown in Table 4. However, each component shown in Table 4, for example, the radical initiator, etc., has been consumed in the reaction, and the copolymer (A1) and neutralizing agent (F) have undergone a neutralization reaction, and therefore are not contained as they are in the bake-curable electrodeposition solution. The evaluation results are shown in Table 4.
[0104] [Evaluation of electrodeposition on metal plate] The obtained bake-hardening type electrodeposition solution 1 was heated to 21°C, and the following anode and cathode were immersed in it and a voltage was applied to form an electrodeposition coating film of about 15 μm on the surface of the anode. Anode: Aluminum plate (material A-1100, size 50mm x 100mm x 1mm thick) Cathode: 18-8 stainless steel plate Applied voltage: DC 140V Application time: 2 minutes The electrodeposition-coated aluminum plate was then taken out and thoroughly washed with water, and then baked and dried at a temperature of 180° C. for 30 minutes, after which various evaluations were carried out.
[0105] [Evaluation of electrodeposition on 3D printed metal objects] Using the obtained bake-hardening electrodeposition liquid 1, the following steps (1) to (7) were carried out in this order to form an electrodeposition coating film of the bake-hardening electrodeposition liquid 1 on the surface of a 3D printer metal model 1.
[0106] (1) Degreasing process for the surface of 3D printed metal objects The 3D printer metal object 1 was immersed in degreasing solution 1 at 50° C. for 3 minutes, and then in degreasing solution 2 at 50° C. for 3 minutes to degrease the surface.
[0107] (2) A water washing process for the surface of 3D printed metal objects The 3D printer metal molded object 1 was immersed in deionized water at room temperature and swung up and down for 60 seconds to improve water washability.
[0108] (3) Immersing the 3D printed metal object in a bake-hardening electrodeposition solution The bake-hardening electrodeposition solution 1 prepared above was poured into an electrodeposition bath and kept at 21°C. While the bake-hardening electrodeposition liquid 1 in the electrodeposition tank was stirred, the 3D printer metal model 1, which had been washed with water and whose surface was still wet, was immersed in the bake-hardening electrodeposition liquid in the electrodeposition tank.
[0109] (4) Removal of air bubbles from the surface of 3D printed metal objects While stirring the bake-hardening electrodeposition liquid 1 in the electrodeposition tank, the immersed 3D printed metal object 1 was rocked up and down for 30 seconds to remove air bubbles adhering to the surface of the 3D printed metal object 1 and to allow the surface of the 3D printed metal object 1 to become familiar with the bake-hardening electrodeposition liquid 1.
[0110] (5) Electrodeposition coating film formation process The stirring of the bake-hardenable electrodeposition liquid 1 and the up-and-down movement of the 3D printed metal object 1 were stopped, and the bake-hardenable electrodeposition liquid 1 was electrodeposited onto the surface of the 3D printed metal object 1 using a constant voltage method under the following conditions. Anode: 3D printer metal model 1 Cathode: SUS304 Applied voltage: 160V Power supply time: 2 minutes After the voltage application was completed, the 3D printer metal model 1 was left to stand in the bake-hardening electrodeposition liquid 1 for 10 seconds, so that the formed electrodeposition coating film was allowed to blend into the surface of the 3D printer metal model 1.
[0111] (6) Rinse and drain the electrocoating film The 3D printer metal model 1 with the electrodeposition coating was removed from the electrodeposition liquid and immersed in deionized water in a circulating water washing tank for 1 minute to be washed. The 3D printer metal model 1 with the electrodeposition coating was removed from the deionized water, drained at room temperature of 20 to 30° C. for about 5 minutes, and then air-blowed to dry the surface.
[0112] (7) Bake hardening process of electrocoating The 3D printer metal model 1 with the electrodeposition coating was placed in an oven at 180° C. and heated for 30 minutes to perform a baking treatment, thereby completing the 3D printer metal model 1 with the electrodeposition coating.
[0113] The 3D printer metal model 1 was replaced with 3D printer metal models 2 to 6, and the same procedure was carried out to complete 3D printer metal models 2 to 6 with electrocoating films. The obtained 3D printed metal objects 1 to 6 with the electrodeposition coating film were then subjected to various evaluations.
[0114] [Examples 2 to 4, 6, and 7, and Comparative Examples 1 to 5] Following the procedures in Table 3 and in the same manner as in Example 1, a bake-hardenable electrodeposition liquid was prepared, and an electrodeposition coating was formed on the surface of a metal flat plate and 3D printer metal models 1 to 6. Metal flat plates with electrodeposition coatings and 3D printer metal models 1 to 5 with electrodeposition coatings were obtained, and evaluated in the same manner.
[0115] [Example 5] Except for the fact that an aluminum plate or a 3D printed metal object was used as the cathode and SUS304 was used as the anode when forming the electrocoating, an electrocoating was formed on the surface of the metal plate and the 3D printed metal object. The same procedures as in Example 1 were carried out in accordance with the descriptions in Table 3 to prepare a bake-hardenable electrocoating liquid, and metal plates with electrocoatings and 3D printed metal objects 1 to 5 with electrocoatings were obtained and evaluated in the same manner.
[0116] [Table 3]
[0117] <Evaluation method> [Calculation of glass transition temperature of copolymer (A)] The Tg of the copolymer (A) was calculated from the following formula, the Tg of the homopolymer of each monomer, and the mass fraction. 1 / Tg A =1 / Tg1×Wt1+1 / Tg2×Wt2+···+1 / Tg n ×Wt n Tg A : Tg of copolymer (A) [absolute temperature K] Tg1, Tg2, ...Tg n : Tg of each monomer [absolute temperature K] Wt1, Wt2, ... Wt n : Mass fraction of each monomer relative to the total amount The Tg of the homopolymer of each monomer is as follows: Monomer (a1): 379K (106℃) ·Monomer (A2): 268K (-5℃) Monomer (b1): 258K (-15℃) Monomer (b2): 328K (55℃) Monomer (c1): 373K (100℃) Monomer (c2): 251K (-22℃) Monomer (c3): 219K (-54℃) Monomer (c4): 188K (-85℃) Monomer (c5): 378K (105℃)
[0118] [Calculation of SP value of copolymer (A)] The SP value of the copolymer (A) was calculated from the following formula, the SP value of each monomer, and the mass fraction. δ = (ΔE / V) 1 / 2 =(ΣΔe i / ΣΔv i ) 1 / 2 δ: SP value of each monomer [(cal / cm 3 ) 0.5 ] ΔE: Cohesive energy [cal / mol] V: Molar volume [cm 3 / mol] Δe i : Evaporation energy of an atom or group of atoms [cal / mol] Δv i : Molar volume of an atom or group of atoms [cm 3 / mol] SP A = δ1 × Wt1 + δ2 × Wt2 + + δ n ×Wt n SPA : SP value of copolymer (A) [(cal / cm 3 ) 0.5 ] δ1, δ2, δ n : δ[(cal / cm 3 ) 0.5 ] Wt1, Wt2, ... Wt n : Mass fraction of each monomer relative to the total amount The δ of each monomer is as follows: Monomer (a1): δ = 14.04 (cal / cm 3 ) 0.5 ·Monomer (A2): δ=14.00(cal / cm 3 ) 0.5 Monomer (b1): δ = 14.48 (cal / cm 3 ) 0.5 ·Monomer (b2): δ=13.47(cal / cm 3 ) 0.5 Monomer (c1): δ = 10.20 (cal / cm 3 ) 0.5 Monomer (c2): δ = 9.77 (cal / cm 3 ) 0.5 Monomer (c3): δ = 9.22 (cal / cm 3 ) 0.5 Monomer (c4): δ = 9.93 (cal / cm 3 ) 0.5
[0119] [Electrodeposition liquid viscosity] The viscosity of the electrodeposition solution was measured using a B-type viscometer (TVB-15M manufactured by Toki Sangyo Co., Ltd.) with an L-type rotor and a low viscosity adapter at a rotation speed of 100 rpm. The symbols in the table have the following meanings: H: over 2.70mPa·s M: 1.80~2.70mPa·s L: Less than 1.80 mPa·s
[0120] [Electrodeposition solution stability] The electrodeposition solution was allowed to stand for 48 hours, and the presence or absence of precipitation or separation was visually determined. The symbols in the table have the following meanings: ○: No sedimentation or separation ×: Sedimentation and separation occurred
[0121] [Electrodeposition coating thickness] The thickness of the electrodeposition coating on the electrodeposition-coated aluminum plate was measured using an eddy current coating thickness meter (ISOSCOPE, manufactured by Fisher).
[0122] [Electrodeposition coating adhesion] In accordance with JIS K 5600-5-6, 10 x 10 = 100 checkerboard-shaped squares were engraved into the electrodeposition coating on an electrodeposition-coated aluminum plate, and the number of squares that did not peel off and the presence or absence of chips were counted by tape application and peeling. The symbols in the table have the following meanings: ◎: 100 pieces without peeling, no chipping ○: 100 pieces without peeling, some chipping ×: No peeling, less than 100 pieces
[0123] [Turnability with electrodeposition coating] The throwing power of the electrodeposition coating on a 3D printed metal object was evaluated. The thickness of the electrodeposition coating film was measured by cross-sectional observation using a scanning electron microscope (SEM). The symbols in the table have the following meanings: ◯: There is no part that is not electrocoated, and the thickness of the thinnest and thickest electrocoating parts is within ±20% of the average thickness. ×: There are areas that are not electrocoated, or the thickness of the thinnest or thickest electrocoating area exceeds ±20% of the average thickness.
[0124] [Magnetic attraction force] The ferromagnetism was evaluated sensorily based on the strength with which a commercially available neodymium magnet was attracted to the electrodeposition-coated aluminum plate. Neodymium magnet used (manufactured by Niroku Seisakusho) Surface magnetic flux density: 370mT Residual magnetic flux density: 1.17T Size: 15mm x 10mm x 4mm thick The symbols in the table have the following meanings: ◎: Very strong adsorption 〇: Strongly adsorbed △: Weakly adsorbed
[0125] [Table 4]
[0126] <Summary of Results> As described above, the bake-hardenable electrodeposition liquid of the present invention has good viscosity and stability, and the electrodeposition coating film exhibits a good balance of uniformity, smoothness, adhesion, throwing power, and magnetization adsorption force due to magnetic force. However, the electrodeposition solutions of the comparative examples showed inferior results in any one of viscosity, stability, uniformity, adhesion, throwing power, and magnetic adsorption force by magnetic force. [Industrial Applicability]
[0127] The bake-hardenable electrodeposition liquid of the present invention can form a coating film with good throwing power by electrodeposition coating at low cost on the surface of a structure having a complex shape, such as that formed by a 3D printer, and can therefore impart insulating properties, rust prevention properties, decoration, etc. to the surface of a structure having a complex shape. Furthermore, the 3D printed metal object having an electrodeposition coating film of the present invention can be used as an actuator part having low coercive force and excellent soft magnetic properties. [Explanation of symbols]
[0128] 1 3D Printer Metal Modeling D Recess structure depth W Recess structure width L Recess structure length
Claims
1. A bake-hardening type electrodeposition liquid for a three-dimensional printer metal object, comprising: the three-dimensional printed metal object has one or more structural parts selected from the group consisting of a groove-shaped recess, a cylindrical recess, a polygonal tubular recess, and a lattice structure, The bake-hardening type electrodeposition liquid contains a copolymer (A), a hardener (B), a solvent (C), and a magnetic powder (D), The copolymer (A) is having a hydroxyl group and a carboxyl group or a tertiary amino group, Water-soluble or water-dispersible, A copolymer of monomer (a), monomer (b), and monomer (c), the mass fraction of the structural unit derived from the monomer (a) in the copolymer (A) is 2 to 15 mass%; the mass fraction of the structural unit derived from the monomer (b) in the copolymer (A) is 2 to 15 mass%; The monomer (a) has a polymerizable carbon-carbon unsaturated bond group and a carboxyl group or a tertiary amino group, The monomer (b) has a polymerizable carbon-carbon unsaturated bond group and a hydroxyl group, the monomer (c) has a polymerizable carbon-carbon unsaturated bond group and is a monomer other than the monomer (a) and the monomer (b); The solvent (C) is an aqueous solvent containing an aqueous organic solvent and water, The bake-hardening type electrodeposition liquid.
2. The mass ratio of the copolymer (A) to the curing agent (B) is 60 / 40 or more and 95 / 5 or less, the total content of the copolymer (A) and the curing agent (B) in the bake-curable electrodeposition liquid is 8% by mass or more and 12% by mass or less; The content of the aqueous organic solvent in the bake-hardenable electrodeposition solution is 0.1% by mass or more and 5% by mass or less, the viscosity of the bake-hardenable electrodeposition liquid, measured at a rotation speed of 100 rpm using a Brookfield viscometer equipped with an L-type rotor and a low-viscosity adapter, is 1.50 mPa·s or more and 2.70 mPa·s or less; The bake-hardenable electrodeposition solution according to claim 1.
3. The copolymer (A) is The glass transition temperature (Tg) is 20 to 40° C. Solubility parameter (SP) value is 10.5 to 11.5 (cal / cm 3 ) 0.5 That is, The bake-hardenable electrodeposition solution according to claim 1.
4. 2. The bake hardenable electrodeposition liquid according to claim 1, wherein the content of said magnetic powder (D) in said bake hardenable electrodeposition liquid is 40 to 170 phr.
5. The monomer (a) has a polymerizable carbon-carbon unsaturated bond group and a carboxyl group, The copolymer (A) has a carboxyl group, The bake-hardening electrodeposition liquid is anionically electrodeposited onto the three-dimensional printer metal object. The bake-hardenable electrodeposition solution according to claim 1.
6. The monomer (a) has a polymerizable carbon-carbon unsaturated bond group and a tertiary amino group, The copolymer (A) has a tertiary amino group, The bake-hardening electrodeposition liquid is cationic electrodeposited onto the three-dimensional printer metal object. The bake-hardenable electrodeposition solution according to claim 1.
7. A three-dimensional printer metal object having a bake-curable electrodeposition coating film, produced using the bake-curable electrodeposition liquid according to any one of claims 1 to 6.
8. A method for forming an electrodeposition coating film, comprising forming an electrodeposition coating film on a surface of a three-dimensional printed metal object using the bake-curable electrodeposition liquid according to any one of claims 1 to 6, the three-dimensional printed metal object has one or more structural parts selected from the group consisting of a groove-shaped recess, a cylindrical recess, a polygonal tubular recess, and a lattice structure, The method includes the following steps (1) to (7) in this order: (1) a step of degreasing the surface of the three-dimensional printer metal object; (2) A step of washing the surface of the three-dimensional printer metal object with water; (3) a step of immersing the three-dimensional printed metal object in the bake-hardening type electrodeposition liquid; (4) removing air bubbles from the surface of the three-dimensional printed metal object; (5) forming an electrodeposition coating film on the surface of the three-dimensional printer metal object; (6) A process of rinsing and draining the electrocoating film; (7) a step of baking and hardening the electrodeposition coating film; Where: Step (3) includes a step of immersing the three-dimensional printer-produced metal object in the bake-hardenable electrodeposition liquid while the surface of the object is wet with water; Step (4) includes a step of stirring the bake-hardenable electrodeposition liquid and moving the three-dimensional printed metal model up and down; Step (5) includes a step of applying the baking hardenable electrodeposition liquid while stopping the stirring of the bake hardenable electrodeposition liquid and the vertical movement of the three-dimensional printed metal model, The method for forming the electrodeposition coating film.
Citation Information
Patent Citations
Anionic electrodeposition coating composition
JP2006111687A
Resin composition for negative cationic electrodeposition photoresist, and coating film formed by electrodeposition coating of the composition
JP2016126174A